The Use of Intra-aortic Balloon Pump in a Real-World Setting: A Comparison between Survivors and Nonsurvivors from Acute Coronary Syndrome Treated with IABP. The Jakarta Acute Coronary Syndrome Registry - Dharma, Surya; Dakota, Iwan; Firdaus, Isman; Wardeh, Alexander J.; Jukema, J. Wouter (International Journal of Angiology, 2013)
Real-world data on acute coronary syndrome (ACS) patients who received intra-aortic balloon pump (IABP) support are limited. The objective of this study was to evaluate the characteristics of ACS patients who received IABP support from a real-world ACS registry. Patients with ACS (N = 121) who received IABP support were enrolled. Characteristics of survivors and nonsurvivors were compared at 30 days. Mortality rate of patients with ACS who received IABP was 47%. The survivors (N = 64) had less often cardiogenic shock (p < 0.001), more often IABP usage as back-up for a revascularization procedure (p = 0.002), less often resuscitation (p = 0.043), and less mechanical ventilator support (p < 0.001) than nonsurvivors. The nonsurvivors had a significantly higher leukocyte count (p = 0.033), a higher serum creatinine level (p < 0.001), a higher blood sugar on admission (p = 0.001), higher creatine kinase MB levels (p = 0.002), and a higher serum uric acid level (p < 0.001), but significantly lower left and right ventricular function (p = 0.014 and p = 0.003, respectively) than survivors. At 30 days, non-ST elevation (STE)-ACS patients had lower mortality rate than ST segment elevation myocardial infarction patients (log-rank test, p < 0.001), and non-STE-ACS patients who had not suffered from cardiogenic shock showed the lowest mortality rate (log-rank test, p < 0.001). By multivariate analysis, a heart rate ≥ 100 beats per minute before IABP insertion was the strongest predictor of 30-day mortality (hazard ratio = 5.69; 95% confidence interval, 1.49 to 21.78; p = 0.011). In ACS patients presenting with either cardiogenic shock, resuscitated, or patients who needed mechanical ventilation suffered from high mortality, despite the use of IABP. IABP appears to be safe and tended to be favorable in noncardiogenic shock ACS patients, particularly non-STE-ACS. A heart rate of ≥ 100 beats per minute prior to IABP insertion was the strongest predictor of 30-day mortality.
Keywords: IABP; ACS; survivor; nonsurvivor